Primary Metabolism during Biosynthesis of Secondary Wall Polymers of Protoxylem Vessel Elements - Ohtani, Misato (Plant Physiol, 2016)
Xylem vessels, the water-conducting cells in vascular plants, undergo characteristic secondary wall deposition and programmed cell death. These processes are regulated by the VASCULAR-RELATED NAC-DOMAIN (VND) transcription factors. Here, to identify changes in metabolism that occur during protoxylem vessel element differentiation, we subjected tobacco (Nicotiana tabacum) BY-2 suspension culture cells carrying an inducible VND7 system to liquid chromatography-mass spectrometry-based wide-target metabolome analysis and transcriptome analysis. Time-course data for 128 metabolites showed dynamic changes in metabolites related to amino acid biosynthesis. The concentration of glyceraldehyde 3-phosphate, an important intermediate of the glycolysis pathway, immediately decreased in the initial stages of cell differentiation. As cell differentiation progressed, specific amino acids accumulated, including the shikimate-related amino acids and the translocatable nitrogen-rich amino acid arginine. Transcriptome data indicated that cell differentiation involved the active up-regulation of genes encoding the enzymes catalyzing fructose 6-phosphate biosynthesis from glyceraldehyde 3-phosphate, phosphoenolpyruvate biosynthesis from oxaloacetate, and phenylalanine biosynthesis, which includes shikimate pathway enzymes. Concomitantly, active changes in the amount of fructose 6-phosphate and phosphoenolpyruvate were detected during cell differentiation. Taken together, our results show that protoxylem vessel element differentiation is associated with changes in primary metabolism, which could facilitate the production of polysaccharides and lignin monomers and, thus, promote the formation of the secondary cell wall. Also, these metabolic shifts correlate with the active transcriptional regulation of specific enzyme genes. Therefore, our observations indicate that primary metabolism is actively regulated during protoxylem vessel element differentiation to alter the cell’s metabolic activity for the biosynthesis of secondary wall polymers.